The Dialectics of Tradition and Innovation: Hybridizing Peer Teaching within the Kitab Kuning Learning Ecosystem - Erfan Habibi; Musyaffa Rafiqie; Moch. Imam Machfudi; Abd. Muhith; Abdul Hamid Achak (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
Kitab Kuning learning in Salaf Islamic boarding schools (pesantren) faces a dialectic between preserving authoritative tradition (sanad, talaqqi) and adopting collaborative pedagogical innovation (peer teaching). This study aims to answer: How is this dialectic manifested in learning experiences, and what kind of hybrid pedagogy model can be developed? This study positions itself within the discourse of pedagogical glocalization, analyzing the negotiation between the traditional structure of pesantren and modern learning approaches through the lens of social construction theory. A phenomenological qualitative study was conducted in two Salaf Islamic boarding schools in East Java, involving 20 students and 4 teachers. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed thematically. The findings indicate that: (1) Peer teaching enhances student agency and metacognitive awareness, yet remains framed within teacher authority; (2) Conventional methods preserve the spirituality of talaqqi but limit critical space; (3) Cultural resistance leads to the adaptation of a “guided musyafahah” model as a form of hybridization. The implication is that Kitab Kuning learning requires a contextual model that integrates authoritative transmission and collaborative exploration.